2010
DOI: 10.1155/2010/250476
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Microparticles in Diabetes Mellitus

Abstract: Background. Endothelial Microparticles (EMPs) are small vesicles shed from activated or apoptotic endothelial cells and involved in cellular cross-talk. Whether EMP immunophenotypes vary according to stimulus in Diabetes Mellitus (DM) is not known. We studied the cellular adhesion molecule (CAM) profile of circulating EMPs in patients with and without Diabetes Mellitus type 2, who were undergoing elective cardiac catheterization. Methods and Results. EMPs were analyzed by flow cytometry. The absolute median n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 35 publications
7
108
1
4
Order By: Relevance
“…These results complement and extend the important findings of Nioks Werner et al [7], who demonstrated that apoptotic EMP are involved in the pathogenesis of ED in CAD. A previous study showed that a CD62E + /CD31 + ratio ≤ 1.0 suggests that endothelial cell apoptosis plays the main role in the vessel damage associated with CAD [8]. Here, we showed that the CD62E + / CD31 + ratio in the CAD group was <1.0; significantly lower than that in the healthy group (p<0.001).…”
Section: Discussionsupporting
confidence: 41%
“…These results complement and extend the important findings of Nioks Werner et al [7], who demonstrated that apoptotic EMP are involved in the pathogenesis of ED in CAD. A previous study showed that a CD62E + /CD31 + ratio ≤ 1.0 suggests that endothelial cell apoptosis plays the main role in the vessel damage associated with CAD [8]. Here, we showed that the CD62E + / CD31 + ratio in the CAD group was <1.0; significantly lower than that in the healthy group (p<0.001).…”
Section: Discussionsupporting
confidence: 41%
“…Type 2 diabetes is especially a chronic inflammatory disease and circulating microvesicles seem to be elevated in these patients [36,37]. It was, therefore, relevant to measure inflammation parameters and microvesicle numbers in patients with diabetes who manifest increased susceptibility to air pollution [29].…”
Section: Discussionmentioning
confidence: 99%
“…T2DM was used as the disease model because of the high risk for vascular complications, and previous works have reported the pathological implications 33,34 and clinical utilities 35,36 of circulating MPs in T2DM patients. Interestingly, both immune MPs (LMPs and NMPs) were strongly correlated to established cardiovascular risk factors, including body mass index, carotid intima-media thickness and triglyceride levels (Po0.05, Po0.01 and Po0.001, respectively) in T2DM patients (Figure 5d), suggesting a link between inflammation and lipid metabolism in diabetes patients.…”
Section: Mps Separation Using Hidffmentioning
confidence: 99%